Strategi Pendidikan Islam Berbasis Seni Budaya di Pesantren Kaliopak Perspektif Hadis - Marlina, Tia; Nur Faiza, Anni; Lessy, Zulkipli; Nur Khotimah, Siti; Mualimin, Muhammad (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
This study aims to explain the strategy of Islamic religious education based on arts and culture at the Kaliopak Islamic Boarding School in Klenggotan, Piyungan, Bantul, Yogyakarta. This research employs a qualitative method through observation, interviews, and documentation, with data validation using source triangulation. The findings indicate that the implemented strategies include direct, interactive, and empirical learning. As a result, students are able to comprehend the material, enhance their piety, develop a love for the Islamic arts and culture of the archipelago, and exhibit commendable character. Supporting factors include the exemplary behavior of the organizers, students’ enthusiasm for learning, support from the surrounding community, a comfortable learning environment, and adequate facilities. Challenges include the caregivers’ busy schedules, limited time, and less conducive activity arrangements. From the perspective of hadith, arts and culture are viewed as tools for fostering beauty, obedience, and monotheism in Islam.